PENGARUH LAMA PENYIMPANAN TERHADAP KUALITAS INTERNAL TELUR AYAM RAS PADA FASE KEDUA - Repilina Sihombing; Tintin Kurtini; Khaira Nova (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
Egg are nutrient-rich livestock products and are needed by the body as a source of protein, fat, andminerals are cheap and affordable for all people. However, the egg is a perishable farm products. Thesecond phase of broiler production was 42–72 weeks to produce eggs which have a large surface area,thin shell, causing release CO2 and H2O through the pores for fast storage, so that the rate of decline ininternal egg quality the faster.The purpose of this study are (1) determine the effect of egg storage time on the internal quality ofeggs and (2) determine the best long shelf against internal quality egg production in the secondphase.This research was carried out on September 25–October 9, 2013 housed in the LaboratoryAnimal Production and Reproduction, Department of Animal Husbandry, Faculty of Agriculture,University of Lampung. This study use a completely randomized design (CRD) with 4 treatments eggstorage time for 1,5, 10, and 15 days. The data obtained were tested in accordance with theassumption of variance. If there was a real variable Duncan test at 5% significance level.The results of this study showed that treatment of egg storage significant effect (P<0,05) on eggweight, HU impairment, an increase in the pH of the egg, and egg yolk color score. Storage time forfive day the best effect on egg weight is lowest at 1,4% and the value of Haugh Units (HU) of 55,4(quality B) compared to the old 10 and 15 days of storage.